2013
DOI: 10.1111/maec.12093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ocean acidification on sponge communities

Abstract: The effects of ocean acidification on lower invertebrates such as sponges may be pronounced because of their low capacity for acid-base regulation. However, so far, most studies have focused on calcifiers. We present the first study of the effects of ocean acidification on the Porifera. Sponge species composition and cover along pH gradients at CO 2 vents off Ischia (Tyrrhenian Sea, Italy) was measured at sites with normal pH (8.1-8.2), lowered pH (mean 7.8-7.9, min 7.4-7.5) and extremely low pH (6.6). There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
42
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 44 publications
9
42
0
Order By: Relevance
“…Leucosolenia produces calcite spicules that are protected in organic sheaths (Jones, ). Our data, however, do not support the prediction that calcareous sponges will necessarily be losers in the event of increased OA, although in naturally high CO 2 sites, siliceous sponges are more successful (Goodwin et al ., ). Previous work has indicated that settlement and recruitment is neither facilitated, nor inhibited by previous colonists in biofouling communities (Watson & Barnes, ; Bowden et al ., ), hence either low pH directly improved conditions for recruitment and growth of our ascidians, or numbers increased because of reduced competition.…”
Section: Discussionmentioning
confidence: 96%
“…Leucosolenia produces calcite spicules that are protected in organic sheaths (Jones, ). Our data, however, do not support the prediction that calcareous sponges will necessarily be losers in the event of increased OA, although in naturally high CO 2 sites, siliceous sponges are more successful (Goodwin et al ., ). Previous work has indicated that settlement and recruitment is neither facilitated, nor inhibited by previous colonists in biofouling communities (Watson & Barnes, ; Bowden et al ., ), hence either low pH directly improved conditions for recruitment and growth of our ascidians, or numbers increased because of reduced competition.…”
Section: Discussionmentioning
confidence: 96%
“…Studies focussing exclusively on the effects of OA at volcanic CO 2 seep sites have reported contrasting results. While sponge diversity was found to increase at low pH sites (pH 7.8–7.9) in the Mediterranean (Goodwin et al ., ), sponge diversity decreased at low pH sites (pH 7.73–8.00) in Papua New Guinea (Fabricius et al ., ), although particular species did become significantly more abundant at sites with active CO 2 bubbling (Morrow et al ., ). Although these studies provide some insight into sponge responses to a changing climate, the co‐occurrence of OW and OA requires studies that consider these factors concurrently (Dupont & Pörtner, ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, it has been suggested that some sponge species may remain unaffected by OA (Durkworth et al ., ; Goodwin et al . ; Morrow et al ., ) and, overall, sponge taxa could benefit from acidic conditions (Bell et al ., ; Morrow et al ., ). However, the lack of knowledge about the mechanisms by which sponges respond to altered pH has become a limiting step in understanding how some sponge species resist OA.…”
Section: Introductionmentioning
confidence: 99%